The dance of anger : a woman's guide to changing the patterns of intimate relationships - Lerner, Harriet Goldhor (William Morrow & Co, an imprint of HarperCollins Publishers, 2014)
Based on the author's clinical experience and workshops she has introduced, this guide helps women understand the causes and patterns of their anger while providing specific alternatives for forging more powerful relationships.